2005
DOI: 10.1080/13548500500093308
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits associated with cancer: A model of subjective and objective outcomes

Abstract: Cancer and its treatment can affect many different aspects of quality of life. As a construct measured subjectively, quality of life shows an inconsistent relationship with objective outcome measures. That is, sometimes subjective and objective outcomes correspond with each other and sometimes they show little or no relationship. In this article, we propose a model for the relationship between subjective and objective outcomes using the example of cognitive function in people with cancer. The model and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 102 publications
1
24
0
1
Order By: Relevance
“…Medical researchers are experimenting with the use of several different pharmacologic agents for preventing and ameliorating cognitive dysfunction associated with cancer treatment, including nerve growth factor, amifostine, methylphenidate, and corticosteroids. 21 However, these treatments may result in additional side effects and sometimes interact harmfully with other prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical researchers are experimenting with the use of several different pharmacologic agents for preventing and ameliorating cognitive dysfunction associated with cancer treatment, including nerve growth factor, amifostine, methylphenidate, and corticosteroids. 21 However, these treatments may result in additional side effects and sometimes interact harmfully with other prescribed medications.…”
Section: Discussionmentioning
confidence: 99%
“…14, 21 We present a modified, simplified form (see Figure 1), which we use to call attention to the way acupuncture may be used as a potential treatment option. The progression of cancer may induce somatic dysfunctions and then structural neurological deficits, as well as psychological distress, the latter arising from anxiety and stress associated with the diagnosis and cancer itself.…”
Section: Chemotherapy-associated Cognitive Dysfunctionmentioning
confidence: 99%
“…Twenty-eight reviews (Ahles & Saykin 2007;Artherholt & Fann 2012;Beauchet 2006;Biegler et al 2009;Chen & Petrylak 2004;Chism & Kunkel 2009;Droz et al 2010;Falci et al 2009;Green et al 2005;Grossmann & Zajac 2011;Gruca et al 2012;Harrington et al 2010;Holzbeierlein 2006;Isbarn et al 2009;Jamadar et al 2012;Janelsins et al 2011;Mitsiades et al 2008;Mohile et al 2009;Mottet et al 2006;Nelson et al 2008;Scherr & Pitts 2003;Sharifi 2005;Trost et al 2013;Tombal 2009;Wefel et al 2004;Wright et al 2006;Ziółkowska et al 2012) described twenty primary studies (Alibhai et al 2010;Almeida et al 2004;Beer et al 2006;Beer et al 2004;Bloomfield & Shilling 2004;Bussiere et al 2005;Cherrier et al 2003;Cherrier et al 2009;DiBlasio et al 2008;Green et al 2002;Green et al 2004;Jenkins et al 2005;Joly et al 2006;Mohile et al 2010;…”
Section: Review Characteristicsunclassified
“…Examples of cognitive dysfunctions that may lead to negative effects on career problem-solving and decisionmaking are delirium, attention, memory, or executive function (Green et al, 2005). However, there is limited research investigating how psychological and vocational constructs influence the career outcomes of this population.…”
Section: Introductionmentioning
confidence: 98%
“…Earlier studies suggested that neurocognitive problems because of surgery, chemotherapy, or radiotherapy may negatively influence CNS cancer survivors' capacity of career problem-solving and decision-making (Green et al, 2005;Kohli et al, 2007;Gehring et al, 2008). Examples of cognitive dysfunctions that may lead to negative effects on career problem-solving and decisionmaking are delirium, attention, memory, or executive function (Green et al, 2005).…”
Section: Introductionmentioning
confidence: 99%